Inhibition of sphingosine-1-phosphate receptor 3 suppresses ATP-induced NLRP3 inflammasome activation in macrophages via TWIK2-mediated potassium efflux - Wang, Yingqin; Wang, Chen; He, Qiaolan; Chen, Guannan; Yu, Jie; Cang, Jing; Zhong, Ming (Frontiers in Immunology, 2023)
Background: Inhibition of sphingosine kinase 1 (SphK1), which catalyzes bioactive lipid sphingosine-1–phosphate (S1P), attenuates NLRP3 inflammasome activation. S1P exerts most of its function by binding to S1P receptors (S1PR1-5). The roles of S1P receptors in NLRP3 inflammasome activation remain unclear. Materials and Methods: The mRNA expressions of S1PRs in bone marrow-derived macrophages (BMDMs) were measured by real-time quantitative polymerase chain reaction (qPCR) assays. BMDMs were primed with LPS and stimulated with NLRP3 activators, including ATP, nigericin, and imiquimod. Interleukin-1β (IL-1β) in the cell culture supernatant was detected by enzyme-linked immunosorbent assay (ELISA). Intracellular potassium was labeled with a potassium indicator and was measured by confocal microscopy. Protein expression in whole-cell or plasma membrane fraction was measured by Western blot. Cecal ligation and puncture (CLP) was induced in C57BL/6J mice. Mortality, lung wet/dry ratio, NLRP3 activation, and bacterial loads were measured. Results: Macrophages expressed all five S1PRs in the resting state. The mRNA expression of S1PR3 was upregulated after lipopolysaccharide (LPS) stimulation. Inhibition of S1PR3 suppressed NLRP3 and pro-IL-1β in macrophages primed with LPS. Inhibition of S1PR3 attenuated ATP-induced NLRP3 inflammasome activation, enhanced nigericin-induced NLRP3 activation, and did not affect imiquimod-induced NLRP3 inflammasome activation. In addition, inhibition of S1PR3 suppressed ATP-induced intracellular potassium efflux. Inhibition of S1PR3 did not affect the mRNA or protein expression of TWIK2 in LPS-primed BMDMs. ATP stimulation induced TWIK2 expression in the plasma membrane of LPS-primed BMDMs, and inhibition of S1PR3 impeded the membrane expression of TWIK2 induced by ATP. Compared with CLP mice treated with vehicle, CLP mice treated with the S1PR3 antagonist, TY52156, had aggravated pulmonary edema, increased bacterial loads in the lung, liver, spleen, and blood, and a higher seven-day mortality rate. Conclusions: Inhibition of S1PR3 suppresses the expression of NLRP3 and pro-IL-1β during LPS priming, and attenuates ATP-induced NLRP3 inflammasome activation by impeding membrane trafficking of TWIK2 and potassium efflux. Although inhibition of S1PR3 decreases IL-1β maturation in the lungs, it leads to higher bacterial loads and mortality in CLP mice.